Oxidative Metalation as a Route to Size‐Mismatched Macrocyclic Complexes: Osmium Corroles1. (24th October 2014) - Alemayehu, Abraham B.; Gagnon, Kevin J.; Terner, James; Ghosh, Abhik
Abstract Heavy‐element corroles are of great interest as optical sensors, near‐IR dyes, phosphors, organic light‐emitting diodes, and anticancer compounds. Insertion of 5d metals into corroles, however, is often a difficult and unpredictable process. Against this backdrop, oxidative metalation of meso triarylcorroles with [Os3(CO)12]/NaN3 in refluxing 1:2 diethylene glycol monomethyl ether/glycol has provided a convenient and relatively high‐yielding route to nitridoosmium(VI) corroles, three of which could be characterized with single‐crystal X‐ray structure analysis.